The -786 T/C polymorphism of the NOS3 gene is associated with elite performance in power sports - Gomez-Gallego, F.; Ruiz, J. R.; Buxens, A.; Artieda, M.; Arteta, D.; Santiago, C.; Rodriguez-Romo, G.; Lao, J. I.; Lucia, A. (European Journal of Applied Physiology, 2009)
The NOS3 gene is a candidate to explain individual variations in health and exercise related phenotypes. We compared genotypic and allelic frequencies of the NOS3 -786 T/C polymorphism (rs2070744) in three groups of men of the same Caucasian (Spanish) descent: (i) elite endurance athletes (cyclists, runners; N = 100); (ii) elite power athletes (jumpers, throwers, sprinters; N = 53) and (iii) non-athletic controls (N = 100). The frequency of the TT genotype was significantly higher in power athletes (57%) than in the endurance (33%, P = 0.017) or control group (34%, P = 0.026). The frequency of the T allele was also higher in power sportsmen (71%) than in their endurance (55%, P = 0.003) and control referents (56%, P = 0.015). No differences were observed between control and endurance groups. In summary, the -786 T/C polymorphism of the NOS3 gene seems to be associated with elite performance in power-oriented athletic events (throwing, jumping, sprinting), with the T allele exerting a beneficial effect. The mechanism by which this allele variant might benefit power performance remains to be elucidated.